The Comparative Pathology of Genetically Engineered Mouse Models for Neuroendocrine Carcinomas of the Lung. Issue 4 (April 2015) - Gazdar, Adi F.; Savage, Trisha K.; Johnson, Jane E.; Berns, Anton; Sage, Julien; Linnoila, R. Ilona; MacPherson, David; McFadden, David G.; Farago, Anna; Jacks, Tyler; Travis, William D.; Brambilla, Elisabeth
Abstract : Introduction: Because small-cell lung carcinomas (SCLC) are seldom resected, human materials for study are limited. Thus, genetically engineered mouse models (GEMMs) for SCLC and other high-grade lung neuroendocrine (NE) carcinomas are crucial for translational research. Methods: The pathologies of five GEMMs were studied in detail and consensus diagnoses reached by four lung cancer pathology experts. Hematoxylin and Eosin and immunostained slides of over 100 mice were obtained from the originating and other laboratories and digitalized. The GEMMs included the original Rb/p53 double knockout (Berns Laboratory) and triple knockouts from the Sage, MacPherson, and Jacks laboratories (double knockout model plus loss of p130 [Sage laboratory] or loss of Pten [MacPherson and Jacks laboratories]). In addition, a GEMM with constitutive co-expression of SV40 large T antigen and Ascl1 under the Scgb1a1 promoter from the Linnoila laboratory were included. Results: The lung tumors in all of the models had common as well as distinct pathological features. All three conditional knockout models resulted in multiple pulmonary tumors arising mainly from the central compartment (large bronchi) with foci of in situ carcinoma and NE cell hyperplasia. They consisted of inter- and intra-tumor mixtures of SCLC and large-cell NE cell carcinoma in varying proportions. Occasional adeno- or large-cell carcinomas were also seen. Extensive vascular and lymphatic invasion and metastases to the mediastinum and liver were noted, mainly of SCLC histology. In the Rb/p53/Pten triple knockout model from the MacPherson and Jacks laboratories and in the constitutive SV40/T antigen model many peripherally arising non–small-cell lung carcinoma tumors having varying degrees of NE marker expression were present (non–small-cell lung carcinoma-NE tumors). The resultant histological phenotypes were influenced by the introduction of specific genetic alterations, by inactivation of one or both alleles of specific genes, by time from Cre activation and by targeting of lung cells or NE cell subpopulations. Conclusion: The five GEMM models studied are representative for the entire spectrum of human high-grade NE carcinomas and are also useful for the study of multistage pathogenesis and the metastatic properties of these tumors. They represent one of the most advanced forms of currently available GEMM models for the study of human cancer.